2018
DOI: 10.1016/j.envres.2017.11.040
|View full text |Cite
|
Sign up to set email alerts
|

Lifetime exposure to ambient air pollution and methylation of tumor suppressor genes in breast tumors

Abstract: We observed suggestive evidence that exposure to ambient air pollution throughout life, measured as TSP and TE, may be associated with DNA methylation of some tumor suppressor genes in breast tumor tissue. Future studies with a larger sample size that assess methylation of more sites are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
1
4

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 68 publications
(78 reference statements)
2
20
1
4
Order By: Relevance
“…NO 2 and PM 10 concentrations were significantly and positively associated with the breast cancer incidence rate in South Korean female population. This result is consistent with previous studies that reported significantly higher risk of breast cancer incidence 5,7,9,11 , and is partly consistent with studies that reported suggestive 6,8,10,12,14,15,27 or null 11,[21][22][23]28 associations between air pollutants and breast cancer. Our study adds evidence of a significant positive association to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…NO 2 and PM 10 concentrations were significantly and positively associated with the breast cancer incidence rate in South Korean female population. This result is consistent with previous studies that reported significantly higher risk of breast cancer incidence 5,7,9,11 , and is partly consistent with studies that reported suggestive 6,8,10,12,14,15,27 or null 11,[21][22][23]28 associations between air pollutants and breast cancer. Our study adds evidence of a significant positive association to the aforementioned studies.…”
Section: Discussionsupporting
confidence: 93%
“…This adds a new layer of evidence for the association between air pollution and breast cancer incidence rates to the previous studies that had case-control or cohort settings. Differences in the significance of the positive association in our study and www.nature.com/scientificreports www.nature.com/scientificreports/ aforementioned studies may be due to the relatively severer air pollution in South Korea (Table 1) compared with the air pollution measured in European 10,23 or North American cohorts 6,8,11,14,22,27 . If so, countries with severe air pollution, such as China or India, may also exhibit significant positive associations that are similar to our result.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…Our inference is that the best way to accomplish a reliable and effective study is follow a combination of various methodologies of quantitative and qualitative research. We therefore conclude that, the most appropriate methods in our study are a mixture of qualitative, quantitative research, longitudinal and cross-sectional research and classification research [1,5,8,11,13,21,23,29,32,33,42,48,52,53,76,79,91,92,95,98,106,113,124,126,129,136,140,142].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, when it evaluated the difference between levels of methylation by age groups no significant results were found (20–39 years old: 42.04 ± 19.12, 40–59 years old: 41.40 ± 17.27; p = 0.9310; Mann–Whitney); (20–30 years old: 39.95 ± 18.63, 31–40 years old: 45.70 ± 19.60, 41–50 years old: 44.39 ± 17.28, 51–59 years old: 39.10 ± 17.04; p = 0.1338; Kruskal–Wallis). Indeed, the literature shows that in spite of external factors such as diet [ 18 ], smoking [ 26 ], alcohol consumption [ 27 ] and air pollution [ 28 ], inner factors such as age and gender have also influence on the DNA methylation profile. Differences in the profile of DNA methylation between males and female have already been observed in skin for miR - 137 gene [ 29 ] and in buccal cells for MMP9 and TIMP - 1 genes [ 30 ].…”
Section: Discussionmentioning
confidence: 99%